El rol del canal Movistar Música en la promoción de los artistas indie limeños (2016-2020) - Castillo Rau, Gerardo Saul (2023)
Between the years 2016-2020, Movistar made its Movistar Música platform available to disseminate and promote the work of national indie artists with great potential. Today that this type of programs and promotion strategies seem to have opted for digital platforms, it is interesting to know what contribution it made to the musical scene and its main protagonists. This study of a mixed nature concludes that the diffusion and efforts of the channel through different programs did not have an impact on the connection with the mass public, since its interests were oriented to a quite specific and limited sector of the population. Despite this, the artists consider it important to have had a space on this platform due to the prestige and value it gave their proposals. For Movistar it was more important to retain the target audience of its offer through and the indie scene of the moment more than fulfilled that function.